The Danger Signal Extracellular ATP Is an Inducer of Fusobacterium nucleatum Biofilm Dispersal - Ding, Qinfeng; Tan, Kai Soo (Frontiers in Cellular and Infection Microbiology, 2016)
Plaque biofilm is the primary etiological agent of periodontal disease. Biofilm formation progresses through multiple developmental stages beginning with bacterial attachment to a surface, followed by development of microcolonies and finally detachment and dispersal from a mature biofilm as free planktonic bacteria. Tissue damage arising from inflammatory response to biofilm is one of the hallmark features of periodontal disease. A consequence of tissue damage is the release of ATP from within the cell into the extracellular space. Extracellular ATP (eATP) is an example of a danger associated molecular pattern (DAMP) employed by mammalian cells to elicit inflammatory and damage healing responses. Although the roles of eATP as a signaling molecule in multi-cellular organisms have been relatively well studied, exogenous ATP also influences bacteria biofilm formation. Since plaque biofilms are continuously exposed to various stresses including exposure to the host damage factors eATP, we hypothesized that eATP, in addition to eliciting inflammation could potentially influence the biofilm lifecycle of periodontal associated bacteria. We found that eATP rather than nutritional factors or oxidative stress induced dispersal of Fusobacterium nucleatum, an organism associated with periodontal disease. eATP induced biofilm dispersal through chelating metal ions present in biofilm. Dispersed F. nucleatum biofilm, regardless of natural or induced dispersal by exogenous ATP, were significantly more adhesive and invasive compared to planktonic or biofilm counterparts, and correspondingly activated significantly more pro-inflammatory cytokine production in infected periodontal fibroblasts. Dispersed F. nucleatum also exhibited significantly higher expression of fadA, a virulence factor implicated in adhesion and invasion, compared to planktonic or biofilm bacteria. This study revealed for the first time that periodontal bacterium is capable of co-opting eATP, a host danger signaling molecule to detach from biofilms. Our results further showed that dispersed F. nucleatum possessed distinct virulence characteristics compared to their biofilm and planktonic counterparts.